Prinzipien guten Unterrichts, Unterrichts- planung und Lehrwerkanalyse - Nied, Martina Lucia (Kritik. Rivista di letteratura e critica culturale, 2023)
What is good teaching? How can I prepare a good foreign language lesson? What makes a good textbook? This paper discusses important principles of good teaching and gives concrete instructions for well-structured lessons which are based on the latest scientific findings in foreign language teaching research. Furthermore, a catalogue of criteria for the analysis of textbooks is presented.